Pengaruh Metode Diskusi Terhadap Minat Belajar Siswa Kelas XI dalam Pendidikan Agama Kristen - Ita Selviana Manik; Johari Manik; Nisma Simorangkir; Tahadodo Waruwu; Dorlan Naibaho (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2025)
The purpose of this study was to determine the positive and significant influence of the discussion method on the interest in learning Christian Religious Education of class XI students of SMA Negeri 1 Sipoholon in the 2024/2025 Academic Year. The method used in this study uses a quantitative approach method. The population is all class XI students of SMA Negeri 1 Sipoholon in the 2024/2025 Academic Year totaling 205 people and a sample of 41 people is determined, which is 20% of the population. Data were collected using a positive closed questionnaire of 42 items. The results of data analysis show that there is a positive and significant influence of the discussion method on the interest in learning Christian Religious Education of class XI students of SMA Negeri 1 Sipoholon in the 2024/2025 Academic Year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.549> rtable (a = 0.05, n = 41) = 0.308 thus it is known that there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value = 4.101> ttable (a = 0.05, dk = n-2 = 39) = 2.021 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂="35","76"+1.13X. b) Regression determination coefficient test (r2) = 30.1%. 3) Hypothesis testing using the F test obtained Fcount> Ftable=(a=0.05, dk numerator k=16, dk denominator=n-2=41-2=39) which is 16.81> 1.51. Thus Ha, namely there is a positive and significant influence of the discussion method on the interest in learning Christian Religious Education of class XI students of SMA Negeri 1 Sipoholon in the 2024/2025 Academic Year, is accepted and H0 is rejected.